2018
DOI: 10.1007/s11916-018-0712-6
|View full text |Cite
|
Sign up to set email alerts
|

Occipital Headaches and Neuroimaging in Children

Abstract: Objective: To investigate the common thinking, as reinforced by the International Classification of Headache Disorders, 3rd edition (beta), that occipital headaches in children are rare and suggestive of serious intracranial pathology.Methods: We performed a retrospective chart review cohort study of all patients #18 years of age referred to a university child neurology clinic for headache in 2009. Patients were stratified by headache location: solely occipital, occipital plus other area(s) of head pain, or no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 43 publications
2
5
0
Order By: Relevance
“…Additionally, these abnormal results can also occur in healthy controls as random results, which is in close concordance with our results [16][17][18][19]. The most common ndings in our study were dilated perivascular space, sinusitis, and cystic lesion (arachnoid cysts).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Additionally, these abnormal results can also occur in healthy controls as random results, which is in close concordance with our results [16][17][18][19]. The most common ndings in our study were dilated perivascular space, sinusitis, and cystic lesion (arachnoid cysts).…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with the results of our study. The mechanism is explained in such a way that it causes facial and head pain due to the action of the trigeminal nerve branch that innervates sensory of the sinuses and nasal mucosa [19]. In other ndings, none of these could directly affect the diagnosis and treatment plan decision for migraine or other headaches.…”
Section: Discussionmentioning
confidence: 99%
“…Sinusitis was the major cause of headaches. According to a previous meta-analysis, the common brain imaging finding in children with headaches included sinusitis, arachnoid cyst, unspecified white matter changes, enlarged cisterna magna, partial empty sella, and choroid plexus cyst [ 16 – 19 ]. Among them, sinusitis is known as a potential cause of headaches in both adults and children.…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35] Of note, while occipital location of headache alone was previously considered a reason to obtain neuroimaging, studies have shown that this does not necessarily indicate a dangerous cause of headache in the absence of an abnormal exam or other concerning symptoms. 51,52 Treatment for Pediatric Migraine…”
Section: Role For Imaging In Workup Of Pediatric Headachesmentioning
confidence: 99%